Analysis of integrons and associated gene cassettes of metallo-{beta}-lactamase-positive Pseudomonas aeruginosa in Malaysia - Khosravi, Y.; Tay, S.T.; Vadivelu, J. (Society for General Microbiology, 2011)
In this study, 90 non-replicate imipenem-resistant Pseudomonas aeruginosa (IRPA) Malaysian isolates collected between October 2005 and March 2008 were subjected to a screening test for detection of the integron and the gene cassette. Class 1 integrons were detected in 54 IRPA clinical isolates, whilst three isolates contained class 2 integrons. Analysis of the gene cassettes associated with the class 1 integrons showed the detection of accC1 in isolates carrying bla(IMP-7) and aacA7 in isolates carrying bla(VIM-2). aadA6 was detected in two isolates carrying bla(IMP-4). Using random amplification of polymorphic DNA analysis, 14 PCR fingerprint patterns were generated from the 32 isolates carrying metallo-β-lactamase (MBL) genes (35.5 %), whilst 20 patterns were generated from the 58 non-MBL gene isolates (64.4 %). Based on the differences in the fingerprinting patterns, two clusters (A and B) were identified among the MBL-producing isolates. Cluster A comprised 18 isolates (56 %) carrying the bla(VIM) gene, whereas cluster B comprised 14 (44 %) isolates carrying the bla(IMP) gene. The non-MBL isolates were divided into clusters C and D. Cluster C comprised 22 non-MBL isolates harbouring class 1 integrons, whilst cluster D consisted of three isolates carrying class 2 integrons. These findings suggest that the class 1 integron is widespread among P. aeruginosa isolated in Malaysia and that characterization of cassette arrays of integrons will be a useful epidemiological tool to study the evolution of multidrug resistance and the dissemination of antibiotic resistance genes.